Benzyl alcohol oxidation with Pd-Zn/TiO2: computational and experimental studies. Issue 1 (31st December 2019) - Nowicka, Ewa; Althahban, Sultan; Leah, Tom D.; Shaw, Greg; Morgan, David; Kiely, Christopher J.; Roldan, Alberto; Hutchings, Graham J.
ABSTRACT: Pd–Zn/TiO2 catalysts containing 1 wt% total metal loading, but with different Pd to Zn ratios, were prepared using a modified impregnation method and tested in the solvent-free aerobic oxidation of benzyl alcohol. The catalyst with the higher Pd content exhibited an enhanced activity for benzyl alcohol oxidation. However, the selectivity to benzaldehyde was significantly improved with increasing presence of Zn. The effect of reduction temperature on catalyst activity was investigated for the catalyst having a Pd to Zn metal molar ratio of 9:1. It was found that lower reduction temperature leads to the formation of PdZn nanoparticles with a wide particle size distribution. In contrast, smaller PdZn particles were formed upon catalyst reduction at higher temperatures. Computational studies were performed to compare the adsorption energies of benzyl alcohol and the reaction products (benzaldehyde and toluene) on PdZn surfaces to understand the oxidation mechanism and further explain the correlation between the catalyst composition and its activity. Graphical Abstract: uf0001